1994
DOI: 10.1093/oxfordjournals.annonc.a058799
|View full text |Cite
|
Sign up to set email alerts
|

Weekly therapy with folinic acid (FA) and high-dose 5-fluorouracil (5-FU) 24-hour infusion in pretreated patients with metastatic colorectal carcinoma

Abstract: Pretreated patients with metastatic colorectal carcinoma, notably those with a primary PR or SD, can probably benefit from weekly high-dose 5-FU/FA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
40
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 20 publications
7
40
0
1
Order By: Relevance
“…However, 45% of patients revealed disease stabilisation lasting for a median interval of 3.2 months. These data are clearly inferior to other agents such as irinotecan (CPT-11) (Rothenberg et al, 1996;Rougier et al, 1997;Van Cutsem et al, 1999) or oxaliplatin plus 5-FU/folinic acid (de Gramont et al, 1997), and appear equal to infusional 5-FU plus high-dose folinic acid (Ardalan et al, 1991;Weh et al, 1994;Hartmann et al, 1998b) alone. Thus, with currently available treatment options for metastatic colorectal cancer, a clear role for infusional 5-FU/bolus MMC cannot be identified (Hejna et al, 2000;Comella et al, 2001;Sobrero et al, 2001;Scheithauer et al, 2002).…”
Section: Discussionmentioning
confidence: 93%
“…However, 45% of patients revealed disease stabilisation lasting for a median interval of 3.2 months. These data are clearly inferior to other agents such as irinotecan (CPT-11) (Rothenberg et al, 1996;Rougier et al, 1997;Van Cutsem et al, 1999) or oxaliplatin plus 5-FU/folinic acid (de Gramont et al, 1997), and appear equal to infusional 5-FU plus high-dose folinic acid (Ardalan et al, 1991;Weh et al, 1994;Hartmann et al, 1998b) alone. Thus, with currently available treatment options for metastatic colorectal cancer, a clear role for infusional 5-FU/bolus MMC cannot be identified (Hejna et al, 2000;Comella et al, 2001;Sobrero et al, 2001;Scheithauer et al, 2002).…”
Section: Discussionmentioning
confidence: 93%
“…It is noteworthy that most of the objective responses observed with 5-FU-based second-line regimens occurred either in patients who had previously responded to 5-FU or in patients who had previously received suboptimal doses of 5-FU. Indeed it appears that previous treatment with 5-FU/LV regimens predicts a poor response to a second 5-FU-based regimen [7].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, most attempts at second-line chemotherapy comprise further 5-FU-modulated treatments. Overall, approximately 10% of patients at most will respond to second-line 5-FU-based chemotherapy, whatever the schedule of 5-FU and/or the modulator agents might be [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the experience of treating colorectal cancer with chemotherapy, alteration of the 5-FU infusion level may lead to a diVerent toxicity proWle. At least two studies reported mild hematologic and non-hematologic toxicities when 5-FU was used as a 24-h infusion combined with leucovorin (AIO regimen), which may increase both the eYcacy of 5-FU and its toxicity [10,11]. In both studies, less than 10% of patients with colorectal cancer had grade 3-4 mucositis and diarrhea, when they received weekly 5-FU administration.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of nonsmall-cell lung cancer patients, weekly use of docetaxel signiWcantly reduced hematologic toxicity without compromising eYcacy [8,9]. Several studies on colorectal cancer reported low incidences of toxicities for weekly 5-FU administration [10,11]. Based on those results, a weekly DCF (wDCF) regimen is considered optimal for treating metastatic gastric cancer, but a full-scale clinical assessment is needed.…”
Section: Introductionmentioning
confidence: 99%